Modified instantaneous power theory control of dynamic voltage restorer powered by photovoltaic system - Asiri, Yousef; Al-Gahtani, Saad F.; Irshad, Shaik Mohammad (Institute of Advanced Engineering and Science, 2023)
Power quality issues have become widespread due to nonlinear electronic converters and loads. Nonlinear components in the power system hamper the power quality, network efficiency and voltage regulation. The power quality issues like sag, swell, and voltage unbalance can be reduced by employing a dynamic voltage restorer (DVR). DVR provides the compensating power from a DC source to minimize the effect of sag, swell, and voltage unbalance. This article presents a power system with DVR using a photovoltaic system (PV) as a DC source instead of a conventional battery source. This article proposes a modified instantaneous power (PQ) control technique to generate the reference signal of load voltage to assure the DVR's superior performance. This modified technique uses an anti-aliasing filter to generate a reference signal. This proposed technique is tested under extreme power quality issues of 80% sag, 20% sag, 120% swell, 170% swell, and voltage unbalance. The DVR is modeled and simulated using MATLAB/Simulink. A comparison is made between the traditional and modified PQ methods from the obtained results. The analyzed results under severe power quality issues suggest that the proposed P-Q control technique is a preferable option for the DVR with PV as a DC power supply.